2014
DOI: 10.2217/fon.14.93
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Detection Methods and Clinical Implications in Lung Cancer

Abstract: Future MedicineUsó, M.; Jantus Lewintre, E.; Sirera Pérez, R.; Bremnes, RM.; Camps, C. (2014)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…NGS technology allows the whole microRNAome of each sample to be analyzed with high sensitivity, a wide dynamic range, high accuracy, and extraordinary technical reproducibility [ 24 , 25 ]. In the cancer research context, NGS technology is especially useful compared to other methodologies because it allows the detection of miRNAs not yet described [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…NGS technology allows the whole microRNAome of each sample to be analyzed with high sensitivity, a wide dynamic range, high accuracy, and extraordinary technical reproducibility [ 24 , 25 ]. In the cancer research context, NGS technology is especially useful compared to other methodologies because it allows the detection of miRNAs not yet described [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been well characterized in human diseases including lung cancer and bladder cancer (52,53). However, only a few lncRNAs have been mechanically and functionally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…They found that CTC detection was associated with the cancer stage. The few studies on circulating miRNA in MCC used RT-qPCR as detection technology [142,150], like for other cancers [151,152]. The MCC miRNome has been investigated mostly in formalin-fixed paraffin-embedded tumor samples [153,154], and the miRNAs identified as MCC-specific could now be evaluated in liquid biopsies.…”
Section: Ctcs and Circulating Mirnasmentioning
confidence: 99%